Selection of Basic Input Variables for Computational Modeling of Brake Shoes. (2016) - Horník, Jakub; Pešlová, Františka; Krum, Stanislav
Abstract: The paper deals with the basic requirements on structural properties combined with material properties for computational modeling of train brake shoes. It is a construction element consisting of base material made of graphitic cast iron and reinforcing steel insertion of simple geometric shape. The structural unit of a "brake shoe" must be functional during train wheels braking. Therefore, it is necessary to design a computational model allowing to simulate operation load and to predict future failure. Because of that, this paper focuses on structural properties with an impact on the construction unit material properties required for computational modeling. Manufacturing technology affects the quality of the final structure whose character may be the cause of the failure initiation. In the presented paper, authors aim to investigate in detail the structure and its imperfections lowering the required properties. These are the factors necessary to take into account in computational modeling of the simulated operating load of the given construction element.